Rational design of biodegradable sulphonamide candidates treating septicaemia by synergistic dual inhibition of COX-2/PGE2 axis and DHPS enzyme - Nada H. El-Dershaby; Soad A. El-Hawash; Shaymaa E. Kassab; Hoda G. Dabees; Ahmed E. Abdel Moneim; Ibrahim A. Abdel Wahab; Mohammad M. Abd-Alhaseeb; Mostafa M. M. El-Miligy (Taylor & Francis Group, 2022)
A new series of co-drugs was designed based on hybridising the dihydropteroate synthase (DHPS) inhibitor sulphonamide scaffold with the COX-2 inhibitor salicylamide pharmacophore through biodegradable linkage to achieve compounds with synergistic dual inhibition of COX-2/PGE2 axis and DHPS enzyme to enhance antibacterial activity for treatment of septicaemia. Compounds 5 b, 5j, 5n and 5o demonstrated potent in vitro COX-2 inhibitory activity comparable to celecoxib. 5j and 5o exhibited ED50 lower than celecoxib in carrageenan-induced paw edoema test with % PGE2 inhibition higher than celecoxib. Furthermore, 5 b, 5j and 5n showed gastric safety profile like celecoxib. Moreover, in vivo antibacterial screening revealed that, 5j showed activity against S.aureus and E.coli higher than sulfasalazine. While, 5o revealed activity against E.coli higher than sulfasalazine and against S.aureus comparable to sulfasalazine. Compound 5j achieved the target goal as potent inhibitor of COX-2/PGE2 axis and in vivo broad-spectrum antibacterial activity against induced septicaemia in mice.